Evolution : components and mechanisms - Zeigler, David, 1950- (Academic Press, 2014)
Evolution: Components and Mechanisms introduces the many recent discoveries and insights that have added to the discipline of organic evolution, and combines them with the key topics needed to gain a fundamental understanding of the mechanisms of evolution. Each chapter covers an important topic or factor pertinent to a modern understanding of evolutionary theory, allowing easy access to particular topics for either study or review. Many chapters are cross-referenced. Modern evolutionary theory has expanded significantly within only the past two to three decades.